2009
DOI: 10.1111/j.1537-2995.2009.02342.x
|View full text |Cite
|
Sign up to set email alerts
|

BLOOD COMPONENTS: Instituting a thawed plasma procedure: it just makes sense and saves cents

Abstract: Our study showed the positive, sustained, impact of implementing a TP SOP. Twelve months after introducing the SOP our Blood Bank and Transfusion Medicine Services' plasma wastage and discard were dramatically reduced, saving thousands of dollars. Initiating a TP SOP just makes sense; it is easy to implement, conserves plasma, and saves cents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 12 publications
0
26
0
Order By: Relevance
“…54 It should be noted that using fixed ratios may increase the wastage of FFPs and PCs, although recently published data indicate that this problem can be adequately addressed. 55 Conversely, most transfusion data suggest that early balanced transfusion decreases overall use of blood products while improving survival. 56 Unquestionably, clear clinical goals for when to stop the MTP should be in place.…”
Section: Discussionmentioning
confidence: 99%
“…54 It should be noted that using fixed ratios may increase the wastage of FFPs and PCs, although recently published data indicate that this problem can be adequately addressed. 55 Conversely, most transfusion data suggest that early balanced transfusion decreases overall use of blood products while improving survival. 56 Unquestionably, clear clinical goals for when to stop the MTP should be in place.…”
Section: Discussionmentioning
confidence: 99%
“…The AB blood type accounts for only 3% of the population but up to 25% of all plasma transfused, with higher proportions in trauma patients. 25 Initial implementation of the increased thawed plasma lifespan (from 24 to 96 hours) significantly decreased discarded plasma, 14,15 and a similar decrease in discard rate of this valuable resource could be expected with expansion to 14 days. And while certain coagulation factors are known to lose significant activity over a 14-day thawed storage time, 5,19 we have shown that a substantial dilution with 14-day TP resulted in enhancement of clot formation compared to whole blood.…”
Section: Discussionmentioning
confidence: 89%
“…This would lead to greater availability of TP at smaller hospitals and limit the amount of plasma wastage at larger hospitals with TP currently available. 14,15 …”
Section: Discussionmentioning
confidence: 99%
“…Nascimento et al [29] documented higher FFP wastage (measurement criteria not stated) in the "1:1:1" cohort of their study. On the other hand, Wehri et al [30] found that having a thawed plasma program reduced plasma discard by 76.3% in their hospital. However, this was achieved in part by extending the shelf-life of pre-thawed refrigerated plasma to 5 days [30].…”
Section: The Controversymentioning
confidence: 96%
“…proper refrigeration before transfusion, increasing the shelf-life of thawed plasma [30], timely deactivation of "1:1:1"), and blood bank policy that accepts returned unused products.…”
Section: The Controversymentioning
confidence: 99%